Hepatitis C in sub-Saharan Africa: the current status and recommendations for achieving elimination by 2030. (December 2017) - Sonderup, Mark W; Afihene, Mary; Ally, Reidwaan; Apica, Betty; Awuku, Yaw; Cunha, Lina; Dusheiko, Geoffrey; Gogela, Neliswa; Lohouès-Kouacou, Marie-Jeanne; Lam, Phillip; Lesi, Olufunmilayo; Mbaye, Papa Saliou; et al.
Summary: In 2016, WHO adopted a strategy for the elimination of viral hepatitis by 2030. Africa, and more specifically, sub-Saharan Africa, carries a substantial portion of the global burden of viral hepatitis, especially chronic hepatitis B and hepatitis C virus infections. The task that lies ahead for sub-Saharan Africa to achieve elimination is substantial, but not insurmountable. Major developments in the management of hepatitis C have put elimination within reach, but several difficulties will need to be navigated on the path to elimination. Many of the challenges faced are unique to sub-Saharan Africa and the development of strategies is complicated by a scarcity of good data from countries and regions within sub-Saharan Africa. However, this hindrance should not act as a barrier to delay interventions in screening, detection, and linkage to care. Moreover, by sharing experiences from across sub-Saharan Africa, countries can create supranational synergies to develop their programmes and work together in a more cohesive manner to tackle the burden of hepatitis C in sub-Saharan Africa. In this Series paper, several issues related to hepatitis C in sub-Saharan Africa are addressed, including prevalence, risk factors, and fibrosis assessment, and recommendations are given by experts from across the region. Simplified diagnostic algorithms and treatment regimens for both HIV co-infected and hepatitis C mono-infected patients are suggested. The recommendations are consensus based and provided to guide the development of programmes in sub-Saharan Africa. Political will and appropriate funding will be required to provide impetus to implement these recommendations.